The Effect of Opiocephalus striatus Extract on Leptin, Adiponectin and COPD Assessment Test Scores on Stable COPD Patients Experiencing Muscle Wasting - Komang Sri Rahayu Widiasari; Susanthy Djajalaksana; Harun Al Rasyid (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2018)
Background: Muscle wasting is one of extrapulmonary manifestations that occur in 20-40% of patients with COPD as a result of an imbalance of protein synthesis and degradation, where it is thought to be a consequence of chronic inflammation. One of the factor that affect muscle wasting is nutritional factor. The purpose of this study is to prove that nutrition therapy can improve inflammation (measured by levels of leptin, adiponectin) further improve muscle wasting and improve the quality of life of patients COPD with muscle wasting. Method: The clinical study design is pre and post auto control quasi experimental in stable COPD patients with comorbid muscle wasting. The experiment was conducted in Pulmonary Outpatient Clinic Dr. Saiful Anwar Hospital and Physiology Laboratory of Medical Faculty Brawijaya University. Chronic obstructive pulmonary disease was diagnosed based on 2014 GOLD criteria. Muscle wasting was diagnosed through examination of the BIA. Levels of leptin and adiponectin was measured using ELISA method, and quality of life was assessed using CAT score. We measured BIA, Leptin, Adiponectin and CAT in 32 COPD patients with muscle wasting, before and after 12 weeks supplementation of Opiocephalus striatus extract 3x1000mg/day. Results: There were significant increased of BMI (p = 0.046), no significant increase of FFMI (p = 0506), a significant decrease in leptin levels (p = 0.000) and a significant increase in adiponectin levels (p = 0.048) and improvement of quality of life (score CAT) (p = 0.000) ) after administration of opiocephalus striatus extract for 12 weeks. Conclusion: Suplementation of Opiocephalus striatus extract for 12 weeks can improve BMI, decrease levels of leptin and increase level of adiponectin resulting in improvement of quality of life in stable COPD patients with muscle wasting.